2022
DOI: 10.1037/xap0000361
|View full text |Cite
|
Sign up to set email alerts
|

How do people perceive sexual harassment targeting transgender women, lesbians, and straight cisgender women?

Abstract: Third-party observers' opinions affect how organizations handle sexual harassment. Prior research has focused on perceptions of sexual harassment targeting straight cisgender women. We examined how targets' sexual orientation and gender identity impact these perceptions. In three preregistered studies, straight cisgender participants imagined a coworker confided that a male colleague had sexually harassed her. The target was a transgender woman, a lesbian woman, or a woman whose sexual orientation and gender i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…When transgender and Black women claim to have been sexually harassed, observers may thus assume that these claimants' use of the term "sexual harassment" refers to gender harassment rather than sexual advance harassment. Consistent with this possibility, Mezzapelle and Reiman (2022) found that when third-party observers learned that a cisgender woman was sexually harassed at work, they tended to assume she had experienced unwanted sexual attention; by contrast, a transgender woman was assumed to have faced gender harassment. Moreover, Hart (2023) demonstrated that a Black woman's claim of an unwelcome sexual advance (harassment typically associated with prototypical women) was rated as less credible than an identical claim made by a White woman.…”
Section: The Sexual Harassment Of Nonprototypical Womenmentioning
confidence: 90%
See 1 more Smart Citation
“…When transgender and Black women claim to have been sexually harassed, observers may thus assume that these claimants' use of the term "sexual harassment" refers to gender harassment rather than sexual advance harassment. Consistent with this possibility, Mezzapelle and Reiman (2022) found that when third-party observers learned that a cisgender woman was sexually harassed at work, they tended to assume she had experienced unwanted sexual attention; by contrast, a transgender woman was assumed to have faced gender harassment. Moreover, Hart (2023) demonstrated that a Black woman's claim of an unwelcome sexual advance (harassment typically associated with prototypical women) was rated as less credible than an identical claim made by a White woman.…”
Section: The Sexual Harassment Of Nonprototypical Womenmentioning
confidence: 90%
“…A more nuanced pattern may emerge when considering sexual harassment claimants' intersecting identities. Prior work on the perceived gender nonprototypicality of transgender and Black women (which focuses on transgender or Black women, not both; e.g., Brassel et al, 2019;Hart, 2023;Mezzapelle & Reiman, 2022) may have tapped perceptions of White transgender women and cisgender Black women -that is, participants in these studies may have envisioned women who are nonprototypical on a single identity dimension (i.e., gender identity or race). Accordingly, it is not clear how third-party perceptions of sexual harassment may be impacted by varying levels of (non)prototypicality on intersecting identity dimensions, or whether (non)prototypicality on one dimension is more consequential.…”
Section: The Sexual Harassment Of Nonprototypical Womenmentioning
confidence: 99%
“…For example, the current work focused on perceptions of two types of sexual harassment, unwanted romantic and sexual advances and sexual coercion. These two types of harassment may be more vulnerable to prototype-related biases compared to the third commonly delineated type of harassment, gender harassment (e.g., derogatory verbal and nonverbal behaviors that communicate hostile attitudes about gender), because they are more closely associated with gender prototypical women and with cis women (Cortina & Berdhal, 2008, Goh et al, 2022Brassel et al, 2019, Mezzapelle & Reiman, 2021. Future work should explore perceptions of additional and overlapping forms of sexual harassment targeting trans women, including hostility based on gender, gender identity, and gender expression (e.g., sexism, misgendering, identity denial, fetishization, pathologization), as well as forms of sexual harassment that are informed by the intersection of additional identity dimensions (e.g., gendered racism and ageism; Matsuzaka & Koch, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%